Radiotracer dose reduction in integrated PET/MR: implications from national electrical manufacturers association phantom studies - Oehmigen, Mark; Ziegler, Susanne; Jakoby, Bjoern W.; Georgi, Jens-Christoph; Paulus, Daniel; Quick, Harald H. (Journal of Nuclear Medicine, 2014)
With the replacement of ionizing CT by MR imaging, integrated PET/MR in selected clinical applications may reduce the overall patient radiation dose when compared with PET/CT. Further potential for radiotracer dose reduction, while maintaining PET image quality (IQ) in integrated PET/MR, may be achieved by increasing the PET acquisition duration to match the longer time needed for MR data acquisition. To systematically verify this hypothesis under controlled conditions, this dose-reduction study was performed using a standardized phantom following the National Electrical Manufacturers Association (NEMA) IQ protocol.All measurements were performed on an integrated PET/MR whole-body hybrid system. The NEMA IQ phantom was filled with water and a total activity of 50.35 MBq of (18)F-FDG. The sphere-to-background activity ratio was 8:1. Multiple PET data blocks of 20-min acquisition time were acquired in list-mode format and were started periodically at multiples of the (18)F-FDG half-lives. Different sinograms (2, 4, 8, and 16 min in duration) were reconstructed. Attenuation correction of the filled NEMA phantom was performed using a CT-based attenuation map template. The attenuation-corrected PET images were then quantitatively evaluated following the NEMA IQ protocol, investigating contrast recovery, background variability, and signal-to-noise ratio. Image groups with half the activity and twice the acquisition time were evaluated. For better statistics, the experiment was repeated 3 times.Contrast recovery, background variability, and signal-to-noise ratio remained almost constant over 3 half-life periods when the decreasing radiotracer activity (100%, 50%, 25%, and 12.5%) was compensated by increasing acquisition time (2, 4, 8, and 16 min). The variation of contrast recovery over 3 half-life periods was small (-6% to +7%), with a mean variation of 2%, compared with the reference setting (100%, 2 min). The signal-to-noise ratio of the hot spheres showed only minor variations over 3 half-life periods (5%). Image readers could not distinguish subjective IQ between the different PET acquisition setups.An approach to reduce the injected radiotracer activity in integrated PET/MR imaging, while maintaining PET IQ, was presented and verified under idealized experimental conditions. This experiment may serve as a basis for further clinical PET/MR studies using reduced radiotracer dose as compared with conventional PET/CT studies.
EVALuna2:10098